Three‐dimensional imaging for the analysis of human epidermal melanocytes. (14th June 2022) - Kim, Dai Hyun; Lee, Se Jeong; Seo, Soo Hong; Ahn, Hyo Hyun; Kim, Byung‐Jo; Sun, Woong; Rhyu, Im Joo
Abstract: Three‐dimensional (3‐D) analysis of human epidermal melanocytes is required for deeper understanding of melanocytic disorders. The purpose of this study was to standardize 3‐D imaging and quantification for the evaluation of epidermal melanocytes. The epidermal specimen was obtained using the suction blister method from a patient with melanocytic nevus on the forearm skin. Cutaneous ACT‐PRESTO, the tissue‐clearing and labeling technique, was subsequently performed. With the 3‐D image analysis program, morphological reconstruction and quantification of selected perilesional and melanocytic nevus areas were possible. The region of melanocytic nevus showed higher numbers of total melanocytic dendrites and similar numbers of cell bodies compared with perilesional area. In addition, the mean area and volume of cell bodies increased in the melanocytic nevus area compared with the results in the perilesional area. The 3‐D evaluation method of human epidermal melanocytes can be applied to investigate novel pathologies related to hyper‐ or hypo‐pigmentary disorders.